Synthesis and Spectral Study of mono-ligand Complexes for Acriflavine with Some Metalions and Evaluation Their Antibacterial Activity - Haya H. Abdul. Hameed (Journal of Global Pharma Technology, 2018)
In this study, a new seven complexes have been prepared from acriflavine (LCl) with metal ions VO (II),Co (II),Ni (II),Cu (II) ,Cd (II), Zn (II) and Hg (II) with mole ratio (M:L) (2:2) all complexes have general composition [M2(L1)Cl4(H2O)4]Cl2, [(VO)2(L1)2(SO4)2(H2O)2]Cl2in ethanol. The ligand and all complexes were characterized by modern spectroscopic(IR, UV_Vis , Mass, atomic absorption), along with elemental microanalysis, magnetic susceptibility measurements and molar conductance. In addition to evaluated their antibacterial activity against two type of bacterial. Based on date for all techniques we suggested that all the prepared complexes have octahedral geometry, the value of antibacterial activity of this prepared complexes showed higher inhibition activity compared to the free ligandKeywords: Acriflavine, Acridine, Acriflavine metal complexes, Biological activity.